2000
DOI: 10.1007/pl00013915
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Phytochrome Mediation in the Low-pH-Induced Root Hair Formation Process in Lettuce (Lactuca sativa L. cv. Grand Rapids) Seedlings

Abstract: The role of light for the low-pH-induced root hair formation process in lettuce seedlings was reported. A high rate of root hair formation was induced by low-pH (pH4.0) treatment under continuous white light, while no root hairs were observed in the dark irrespective of pH conditions. The fluence requirement for root hair initiation was lower than that for root hair elongation, indicating that two different mechanisms operate in the photoinduction of mature root hairs. With regard to root hair initiation, red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…In our previous study, we found that root hair formation occurred on seedlings that were grown at pH 4.0 under white light, but not on seedlings in the dark even when they were grown at pH 4.0 (De Simone et al 2000). This suggests that light is essential for the process of root hair initiation.…”
Section: Effects Of Light Irradiation On the Expression Of The Acs Genesmentioning
confidence: 98%
See 4 more Smart Citations
“…In our previous study, we found that root hair formation occurred on seedlings that were grown at pH 4.0 under white light, but not on seedlings in the dark even when they were grown at pH 4.0 (De Simone et al 2000). This suggests that light is essential for the process of root hair initiation.…”
Section: Effects Of Light Irradiation On the Expression Of The Acs Genesmentioning
confidence: 98%
“…6 The effects of light on ethylene production from seedlings. Following pre-culture at pH 6.0 in the dark, the seedlings were cultured at pH 4.0 in the dark for 3 h to maximize sensitivity to light (De Simone et al 2000). The seedlings were subjected to red (open square), blue (open triangle), or white (open circle) light for 30 min, and then returned to the dark condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations